Assessment of correlation of fatigue in patients of rheumatoid arthritis using bristol rheumatoid arthritis fatigue multidimensional questionnaire score with disease activity – An Indian experience - Harpreet Singh; Kusum Yadav; Ritu Sangwan (Indian Journal of Rheumatology)
Background: Fatigue affects 40%–80% patients of rheumatoid arthritis (RA), impairing their quality of life. Objectives: The aim of this study was to assess fatigue by means of Bristol RA Fatigue Multidimensional Questionnaire score (BRAF-MDQ) and correlate it with the disease activity of RA patients. One hundred RA patients (as per American College of rheumatology 1987 criteria) having no underlying other chronic disease were evaluated at baseline (M0), 1 month (M1), and 3 months (M3) for fatigue (using BRAF-MDQ) and disease activity Disease Activity Index 28 (DAS-28) and Clinical Disease Activity Index (CDAI). The correlation between fatigue score and disease activity score was evaluated. Results: Fatigue score (BRAF-MDQ) decreased from 19.28 ± 13.846 at baseline to 17.46 ± 13.56 at M1 and 13.27 ± 11.633 at M3, respectively (P < 0.001). Similarly, there was significant decrease in disease activity of DAS-28 from 4.439 ± 1.41 at baseline to 3.715 ± 1.655 at M1 and 3.668 ± 1.46 at M3; while CDAI reduced from 18.82 ± 14.314 at baseline to 14.16 ± 12.611 at M1 and 11.65 ± 11.769 at M3, respectively (P < 0.001). There was a positive significant correlation (P value < 0.001) between BRAF-MDQ score and DAS-28 score (r = 0.503; 0.687 and 0.680) and CDAI score (r = 0.642,0.728 and 0.732) at baseline, 1 month, and 3 months, respectively. Multivariate analysis showed that CDAI (M0) was a significant factor affecting BRAF-MOQ score at follow-up of 3 months (M3) with beta coefficient of 0.872, P < 0.0001. Conclusion: The results of the present study indicate that fatigue quantum is related to disease activity and should be evaluated at the time of diagnosis. BRAF-MDQ is a simple, yet effective patient reported outcome questionnaire which assessed the fatigue quantum. Routine assessment of fatigue through BRAF-MDQ along with assessment of disease activity will be a holistic approach in management of RA.